Minimum quality standard regulation and entrepreneurial innovation. Issue 2 (8th November 2018) - McCannon, Bryan C.
Abstract : Purpose: The purpose of this paper is to explore the impact that minimum quality standards have on product quality when entrepreneurial innovation is considered. Design/methodology/approach: The author develops a game-theoretic model. It is a standard vertical product differentiation model, but incorporates a minimum quality standard and uncertain entrepreneurial innovation. Findings: While the minimum quality standard increases the expected quality of the low-quality product, under reasonable circumstances the expected quality of the high-quality good decreases. Thus, average quality can decrease with regulation intended to increase product quality. Research limitations/implications: Past research on minimum quality standards does not consider its impact on entrepreneurial effort when their innovation investments lead to uncertain outcomes. Practical implications: Minimum quality standard regulation can have counterproductive impacts if the impact on entrepreneurs is not considered. The regulation can disincentivize entrepreneurs leading to lower quality products. Social implications: Regulation can be welfare reducing. Originality/value: This paper is the first to incorporate entrepreneurial innovation into a product quality model to explore the impact of minimum quality standard regulation.